Improving Primary School Students Critical Thinking Abilities with the Help of Online Media: Effective Learning Strategies in Elementary Schools - Susanto, Ratnawati; Hapudin, Muhammad Soleh (Universitas Pendidikan Indonesia, 2024)
The lack of adequate emphasis on developing primary school students' critical thinking skills in the curriculum is a problem that requires special attention with the help of online media. Integrating critical thinking concepts into the curriculum can help elementary school students develop the analytical and evaluative skills necessary to understand social reality. The main aim of this research is to analyze the effectiveness of online learning methods, especially in the context of online media use among elementary school students. The research method used is mixed research which combines quantitative and qualitative approaches. The number of respondents was 98 elementary school students. Data collection techniques include surveys, interviews, observation, and documentation. Data analysis was carried out using SPSS version 26.0 software to simplify and manage the data. The research results show that the majority of elementary school students have good analysis, synthesis, problem solving, and drawing conclusions skills, but there is still room for improvement. In conclusion, online media is effective in improving elementary school students' critical thinking skills. The implication is that collaboration between educators, educational institutions, and related parties is very necessary to support the optimal development of students' critical thinking skills.